Copper-catalyzed cyclization of 2-cyanobenzaldehydes and 2-isocyanoacetates: an efficient strategy for the synthesis of substituted 1-aminoisoquinolines12. Issue 59 (5th July 2018) - Bao, Wen; Wang, Jun-Qi; Xu, Xue-Tao; Zhang, Bang-Hong; Liu, Wei-Ting; Lei, Lin-Sheng; Liang, Huan; Zhang, Kun; Wang, Shao-Hua
Abstract : An efficient strategy for the synthesis of substituted 1-aminoisoquinoline has been developed. Abstract : A Cu(acac)2 -catalyzed cyclization reaction of 2-cyanobenzaldehydes with 2-isocyanoacetates has been successfully developed providing an efficient strategy for the synthesis of substituted 1-aminoisoquinolines. The reaction proceeds smoothly under mild conditions with high efficiency, and might provide an alternative strategy for the synthesis of 1-aminoisoquinoline containing molecules.